Fatherland - Becker, Manfred (Barna Alper Productions, 2006)
Verzio FF Submission Fatherland is a personal essay on history and memory. It is Manfred Becker's personal quest to understand his German-Canadian identity. Discussions with his German father and with his young son in Canada reveal three generations caught on the wrong side of history.